Design and Experimental Study of a Large Spherical Tank Wall Paint Removal Robot - Yang Huailin; Liu Chunhua; Chen Xiaohui; Deng Xiandong; Gao Runzhi; Xia Yi; Zang Hongbin (Jixie chuandong)
In order to solve the problem of polishing three-layer high strength epoxy paint on the surface of large spherical tank pressure vessels, a large spherical tank wall paint removal robot is designed, and the experimental research on it is carried out. The robot mainly includes a wall climbing and adsorption system and an adaptive grinding system. By studying the permanent magnet of Halbach array, the relation between the adsorption force of the permanent magnet of track structure and the working clearance is simulated and analyzed, and a wall climbing adsorption system with stable adsorption and superior obstacle climbing performance is developed. According to the grinding condition of the curved wall, an adaptive grinding system based on current feedback is designed, and various steel wire grinding rollers are developed by analyzing the mechanical model of the steel wire grinding roller. The robot is tested, and the polishing effect is good. The robot can polish the epoxy paint and show the metallic luster, and its efficiency is 3-10 times that of the manual grinding. A new polishing tool is proposed for ball tank high-strength epoxy paint polishing, which ensures the polishing quality and improves the polishing efficiency.